Development of hierarchical and phosphorous-modified HZSM-5 zeolites by sequential alkaline/acid treatments and their catalytic performances for methanol-to-olefins. (October 2020) - Tanaka, Shunsuke; Fukui, Ryosuke; Kosaka, Azusa; Nishiyama, Norikazu
Graphical abstract: Highlights: An efficient method based on sequential desilication and dealumination, resulting in large-scale synthesis of hierarchical HZSM-5. H3 PO4 treatment for desilicated HZSM-5 enabled to introduce phosphorous in the zeolite framework. The catalytic performance in MTO reaction was improved by introduction of mesopores and phosphorous modification in HZSM-5. Abstract: An efficient and simple method was proposed to synthesize hierarchical and phosphorous-modified HZSM-5 zeolites by sequential alkaline and acid treatment. In the first NaOH alkaline treatment, intracrystalline mesoporosity was introduced into the zeolites by the crystal defect formation and growth of crystal defects due to desilication. The excessive defect growth caused amorphization of the zeolites, dramatically decreasing their surface area and micropore volume. The aluminum-related debris resulting from the desilication deposited on the extra-framework positions and had a dramatic influence on the crystallinity and microporosity of the zeolites. In the subsequent H3 PO4 treatment for the alkaline-treated HZSM-5, the deposited extra-framework aluminum species were selectively removed, thus increasing the micropore volume and surface area of the zeolites. Along with the dealumination, the phosphorous species were introduced into the framework to occupy the silicon sites, leading to a crystalline structure repair. The post-treatments could modify the structural and acidic properties of the HZSM-5 zeolite. Catalytic tests showed that the hierarchical and phosphorous-modified HZSM-5 zeolite exhibited higher methanol conversion and propylene selectivity in methanol-to-olefins reactions over a longer period compared with the parent HZSM-5.